E-LEARNING MOODLE, MEDIA PEMBELAJARAN FISIKA ABAD 21 - Anggraeni, Desak Made; Sole, Ferdinandus Bele (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: Moodle E-Learning, the 21st Century Physics Learning Media] A distinctive characteristic of 21st-century learning is digital communication, meaning that the learning process is no longer face to face course between teachers and students but is more of an internet-based (e-learning) modern learning. The process of implementing e-learning requires a Learning Management System (LMS) which functions to regulate the management of learning. One of the LMS that can be used in organizing e-learning learning is moodle. Moodle e-learning can be used as a medium to improve the quality of interactive learning and support for the implementation of blended learning. Through e-learning moodle learning material can be accessed anytime and anywhere, besides that the material can be enriched with various learning resources including multimedia, which can be quickly updated by the instructor. In addition, the facilities offered in moodle e-learning learning are able to display learning materials that are abstract in nature into material that can be witnessed in person. Material samples that are mostly abstract are material on physics subjects. Therefore, moodle electronic learning is expected to be able to help students master the concepts in physics learning.